2013
DOI: 10.1177/0885412212471562
|View full text |Cite
|
Sign up to set email alerts
|

Convergence, Divergence, or Constancy of Spatial Planning? Connecting Theoretical Concepts with Empirical Evidence from Europe

Abstract: Spatial planning across much of the world is experiencing reform in response to common challenges of globalization, sustainable development, economic competitiveness, economic reforms, and demographic change. In Europe, greater transnational networking and cooperation on spatial planning, often facilitated by European initiatives, have resulted in planning policy makers at different levels being increasingly influenced and exposed to policies and practices from elsewhere. These processes might be assumed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 102 publications
0
18
0
4
Order By: Relevance
“…Cultural change can also be recognized in altered paradigms or "programmatic ideas". Here, the EU or other intergovernmental organizations become a cognitive and Planning Culture 11 normative frame providing orientation to the logics of meaning and action (Gualini, 2003;Böhme and Waterhout, 2008;Stead, 2013) as the "internationalization" of planning professionals indicates. Furthermore, changes in planning practices and cultures can take place as a (endogenous) result of "institutional self-transformation" (Gualini, 2003, pp.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Cultural change can also be recognized in altered paradigms or "programmatic ideas". Here, the EU or other intergovernmental organizations become a cognitive and Planning Culture 11 normative frame providing orientation to the logics of meaning and action (Gualini, 2003;Böhme and Waterhout, 2008;Stead, 2013) as the "internationalization" of planning professionals indicates. Furthermore, changes in planning practices and cultures can take place as a (endogenous) result of "institutional self-transformation" (Gualini, 2003, pp.…”
Section: Resultsmentioning
confidence: 98%
“…Looking at, for example, Germany or the Scandinavian countries (Othengrafen, 2012), the principles of reducing regional disparities, providing equal living conditions and nationwide comprehensive public approaches and services become apparent. This is rooted in the specific social model of these countries (Nadin and Stead, 2008;Stead, 2013). In contrast, questions of "social justice" do not yet appear to be particularly clear in the Eastern European states, nor is the "role of the public" clearly defined (Staniunas, 2009), including the social model and its implications.…”
Section: Planning Environmentmentioning
confidence: 92%
See 1 more Smart Citation
“…At the same time, participatory practices in these countries have encountered various problems, such as public agencies' limited capacities to use participatory approaches meaningfully (Zacharchenko & Goldenman, 2004). These problems derive not only from the historical patterns of formal institutions (e.g., legislation) or from a potentially low interest in participation on the part of the stakeholders but also from the administrative culture, which affects policy choices and may carry path-dependent ways of thinking among public officials (Stead, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From the information recipients' perspective, Stead (2012Stead ( , 2013 concluded that the scope of policy transfer in spatial planning within Europe is limited due to substantial differences in the economic, political, and social situation of member states. In transport, Marsden and Stead (2011) found that the motivation for learning from others is strongly bounded to funding opportunities and that policy transfer is sometimes introduced for political reasons, to legitimate conclusions already reached by an organization.…”
Section: Difficulties Of Policy Transfer and The Exchange Of Best Pramentioning
confidence: 99%